Breaking Free from Your Fetal Chains: A Case-Based Review of the Literature on Gamma Chain Variant Hemoglobinopathies - Pearl Mary Varughese; Sajan Thomas; Sheela Nampoothiri; Perraju Bendapudi (Korean Society of Neonatology, 2023)
Methemoglobinemia is a dyshemoglobinemia characterized by cyanosis and reduced oxygen saturation with increased methemoglobin values. The etiology may be congenital or acquired, with the latter being more common. We report a case of a full-term neonate who presented with transient cyanosis and methemoglobinemia caused by a mutation in the gamma chain of fetal hemoglobin.